Spontaneous abortion and work with visual display units. - Roman, E; Beral, V; Pelerin, M; Hermon, C (1992)
OBJECTIVE: To determine whether women who work with visual display units are at increased risk of spontaneous abortion. DESIGN: Case-control study. SETTING: Women were recruited during the three years 1987-9 from the Royal Berkshire Hospital in Reading, and from a large group practice situated within the hospital's catchment area. SUBJECTS: Cases were 150 nulliparous working women with a clinically diagnosed spontaneous abortion and controls were 297 nulliparous working women attending for antenatal care. MAIN OUTCOME MEASURES: Cases and controls were contacted and personally interviewed using the same structured questionnaire. Exposure to visual display units (VDUs) at work was assessed from information supplied at interview. RESULTS: No evidence of an increased risk of spontaneous abortion was found in women who reported that they used a VDU at work compared with women who reported that they did not (odds ratio (OR) = 0.9, 95% confidence interval (95% CI) = 0.6-1.4); and no relation with the amount of time spent actively using a VDU was evident (OR = 0.9, 95% CI = 0.5-1.6 for women who worked with a VDU for 21 hours or more each week). No effect of passive exposure to VDUs at work was found (OR = 0.9, 95% CI = 0.6-1.6 for women who reported working less than 10 feet away from a VDU that was usually switched on). These findings were not explained by maternal age, marital state, housing tenure, partner's social class, educational level, smoking, alcohol consumption, or number of previous spontaneous abortions. CONCLUSION: Given the findings and their consistency with the results from other recent studies it is concluded that pregnant women who work with VDUs are not at increased risk of clinically diagnosed spontaneous abortion. For the many women who use VDUs in their jobs, this finding provides reassurance.